(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Both religion and ideologies are both systems of beliefs and built on a dual interpretation of the World and the existence of an elsewhere heavenly or terrestrial. Both give a sense to life salvation in the Next World for religions, happiness and human fulfillment here below for ideologies. At the same time, they deeply differ. Religions generally rely on a dual conception of human nature, when ideologies stress its unity and its materiality. For religions and ideologies, the existence, beyond or below observable realities of a more real world, serve as a model for the people living here and now. They also introduce norms and objectives in individual and collective life. Because of these similarities and differences, religions and ideologies are at the same time complementary and competitive. The analysis of their competition and interaction explains their contemporary evolution.